Implementation of an Automatic Goods Delivery Scheduling System using a Heuristic Algorithm for Sinar Terang Buliding Store BSD - Fauziana, Cantika Ayu; Galuh Saputri (LPPM Politeknik Aceh Selatan, 2026)
This research aims to develop an automated delivery scheduling system for Toko Bangunan Sinar Terang BSD by applying a heuristic algorithm as an optimization approach for scheduling and route planning. The previous manual scheduling process often caused various inefficiencies, such as schedule conflicts, suboptimal route selection, longer travel times, and ineffective vehicle utilization. To address these issues, this study implements a heuristic algorithm capable of generating near-optimal solutions with fast computational time, especially for complex scheduling and distribution problems.The research process includes several stages: requirements analysis, system design, heuristic algorithm implementation, and system testing. The system is designed with a simple interface and structured workflow to ensure ease of use for store administrators. Black box testing demonstrates that all system functions operate according to the design, including data input, route determination, and automatic schedule generation. The implementation results show significant improvements in delivery efficiency, indicated by faster scheduling time, more optimal delivery routes, and better fleet utilization compared to the manual method. Therefore, the application of heuristic algorithms in the delivery scheduling system has proven effective in enhancing punctuality and service quality at Toko Bangunan Sinar Terang BSD. This study is expected to serve as a foundation for future system development, such as GPS integration and the use of more advanced optimization algorithms.